Determinants of Commercial Bank Profitability in Malaysia and Singapore - Rasiah, Devi Naga (2002)
Commercial banks in Malaysia and Singapore have played an important role in the tremendous economic development that has taken place in the region over recent years. In the light of these developments, the objective of this study is to identify the determinants of profitability of commercial banks in Malaysia and singapore. The determinats of profitability and theories thereof used in this study are those frequently described in conventional banking studies and literature. The data for the studies have been extracted from the annual reports of sixteen local commercial banks in Malaysia and ten local commercial banks in Singapore. The period under purview covers financial statements for ten years from 1988 to 1997. The profitability determinants were basically divided into two main categories, namely the internal determinants and the external determinants. The internal determinants include management controllable factors such as liquidity, investment in securities, investment in subsidiaries, loans, non-performing loans, and overhead expenditure. Other determinants such as savings, current account deposits, fixed deposits, total capital and capital reserves, and money supply also play a major role in influencing the profitability. Similarly, external determinants includes those factors which are beyond the control of management of these institutions such as interest rates, inflation rates, market growth and market share. In order to incorporate the internal and external determinants into a single profitability model, it was necessary to include dummy variables to take account of inter-firm and inter temporal differences in the intercept. Thus, pooled regression analysis was applied to a linear model to analyse the profitabilty determinants of Malaysian and Singaporean commercial banks. Briefly the findings indicated that local commercial banks should focus their attention on strategies such as good mangement, a conservative lending policy , a well managed investment portfolio with good liquidity , productivity management, an outstanding of securities portfolio management and tight control over operating expenses to increase profitability. Several promising areas for future research are identified in this study such as interest rate spread or margin can be used as an exploratory variable in place of just market interest rates. Secondly, the variables loans portfolio may be used for bank management in structuring a sound, stable and profitable portfolio. Future research may be extended to iinclude foreign banks in Malaysia and Singapore in their samples.